Selected anthropometric characteristics and body composition of female volleyball players in cadet, junior and senior national team of Slovenia - Zadraznik, M. (Kinesiologia Slovenica, 2022)
Certain morphological characteristics and motor abilities are systematically monitored in Slovenian volleyball teams of different age categories. The study aimed to determine selected anthropometric dimensions and the body composition of 46 members of the cadet, junior and senior women`s volleyball national teams. Anthropometric characteristics were measured using the NX-16 [TC]2 3D-technology for body scanning. Body height was measured using an anthropometer, body mass was weighed using scales, and the body mass index (BMI) was calculated. By using an electrical bioimpedance (EBI) Inbody 720 tetrapolar, 8-point electrode system (Biospace Co., Ltd.), we established percentages of skeletal muscle mass and fat mass as well as body water percentage. The differences among the results for female volleyball players of various categories in terms of body height and body mass are small. Likewise, the body composition results are similar in all three age categories. We also investigated whether the results of anthropometric variables of the upper body differ statistically significantly among individual categories. We identified statistically significant differences between cadet women and senior women in terms of right forearm circumference (p = 0.04). Cadet women (24,62 cm) have a smaller forearm circumference than senior women (25,08 cm). Statistically significant differences were also established between cadet women and junior women in terms of right upper arm circumference (p = 0.03). Junior women have a statistically significantly larger left upper arm circumference. No statistical significance was recorded with respect to other variables. The results obtained are generally similar to those from studies by other authors.